2018
DOI: 10.1002/ldr.2890
|View full text |Cite
|
Sign up to set email alerts
|

Modeling variations in soil salinity in the oasis of Junggar Basin, China

Abstract: Soil salinization leads to a significant degradation for oasis land. Variations in soil salinity are controlled by geologic, geomorphic, climatic, and hydrologic factors that are scale dependent. Many factors characterize soil salinity and its variations. Empirical mode decomposition (EMD) and correlation analysis are usually applied to examine the variations of soil salinity at different scales. However, few researches have been conducted on the modeling of these variations among different scales that require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Therefore, when exploring the degree to which other factors influence the spatial variability of soil salinity and moisture, the interaction between factors needs to be studied further. Secondly, spatial variation of soil properties is scale specific, so the factors that affect soil properties at different scales are different [36,38]. Therefore, the relationship between spatial variability of soil salinity and moisture and topographic factors in large-scale regions should be further studied and considered in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, when exploring the degree to which other factors influence the spatial variability of soil salinity and moisture, the interaction between factors needs to be studied further. Secondly, spatial variation of soil properties is scale specific, so the factors that affect soil properties at different scales are different [36,38]. Therefore, the relationship between spatial variability of soil salinity and moisture and topographic factors in large-scale regions should be further studied and considered in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are some differences in the spatial variation of soil salinity and moisture in different scales [36,37]. Ma, et al [38] indicated that the variation of soil salinity is controlled by topographic, climatic, and hydrological factors at the scale. Ren, et al [39] explored the correlation between soil salinity with groundwater, topography, irrigation, and other factors with three scales.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Approximately 1.128 billion hectares of global lands were affected by soil salinization [2], and in China, salinized areas accounting for approximately 9 percent of the national land resources [3,4]. Major causes of soil salinization can be separated into two ways: one way from primitive soluble saline water, scarce precipitation, and intense evaporation and the other way from shallow groundwater levels, excessive agricultural activities, and flooding irrigation agriculture [5,6]. Quantitative analysis of salt-affected land is one of the effective methods to evaluate the extent of soil salinization, and there is a wide divergence in the embedding temporal and spatial dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…In the arid region, the spatial heterogeneity of soil was significant, which might result in the underestimation of SMC (Thevs et al 2015;Zhang et al 2017). Studies on the soil properties in arid areas have achieved similar results (Ding et al 2018;Ma et al 2018). In recent years, the uncertainties of the ELM method were reviewed by Liu and Lin (Lin et al 2015;Liu et al 2015), especially for the different activation functions and subsequent robustness.…”
Section: Discussionmentioning
confidence: 99%
“…SMC is the main factor that limits the growth of crops to an oasis in this region. Furthermore, increasing human activities in recent years have led to regional SMC imbalances and increased soil salinization within the oasis (Ma et al 2018;Wu et al 2015). During the implementation of sustainable soil management practices and precision agriculture, understanding the spatial distribution of SMC is essential for determining the regional drought situation and measuring water and salt transport in soils.…”
Section: Introductionmentioning
confidence: 99%